CHARACTERISTICS OF LIPID METABOLISM IN PATIENTS WITH TYPE 1 DIABETES, DEPENDING ON THE AVAILABILITY OF DIABETIC MICROANGIOPATHY AND DIET - Yu. G. Samoilova; Ye. V. Yurchenko (Бюллетень сибирской медицины)
Was investigated 67 children (36 boys and 31 girls) in age from 6 to 18 years old, with type 1 diabetes patients who were treated at the Children's Hospital Endocrinology number 1 inTomsk, average age of the boys at the time of the survey amounted to (13.0 ± 0.4) years, girls – (13.5 ± 0.4) years. All children diagnosed with type 1 diabetes were under subcompensation. Clinical evaluation of patients included a medical history, physical examination, evaluation of physical development. A study of lipid profile (high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL), cholesterol (TC), triglycerides (TG), atherogenic index). Screening for diabetic retinopathy was performed by examining the fundus by direct ophthalmoscopy after pupil dilation. Diagnosis of diabetic nephropathy, retinopathy performed according to the classification. Patients were divided into groups depending on the presence of complications, and the level of compensation lipid metabolism (children with satisfactory compensation of lipid metabolism (total cholesterol level less than 5.2 mmol / l), children with poor compensation lipid metabolism (total cholesterol above 5.2 mmol / l)). Nature of the subjects studied nutrition using  a questionnaire drawn up on the basis of the standard dietary questionnaire program CINDI, allowing to evaluate the eating habits by examining the frequency of intake of various foods, food preferences and priorities. Products, according to the lipid-lowering diet on the recommendations of the European Society for atherosclerosis were combined and divided into groups according to frequency of use: commonly used products, and rarely use the products. Mathematical treatment of the results was performed using the software package Statistica 5.5 for Windows. In the first phase expected to total group performance statistics – the arithmetic mean value M and the error of the mean m, as well as visualization of the distribution of values was performed using frequency histograms. To select a criterion to assess the significance of paired differences check compliance form normal distribution using the criterion χ2, and also controlled the general equality of variances using the F-test Fisher. Given that these conditions are satisfied only part of the empirical distributions of features tested the hypothesis that the general average in all cases was performed using Mann–Whitney U-test for independent variables. Null hypothesis was rejected when p < 0.05.In the study of lipid metabolism in patients with type 1 diabetes, no increase in the level of cholesterol, triglycerides, HDL, LDL and VLDL – cholesterol in patients with a combination of diabetic nephropathy and retinopathy compared with patients with type 1 diabetes without diabetic microangiopathy. Investigation of the nature of power in patients with type 1 diabetes, allowed us to estimate its impact on lipid metabolism.